In Vitro and Randomized Controlled Clinical Study of Natural Constituents' Anti-HPV Potential for Treatment of Plantar Warts Supported with In Silico Studies and Network Analysis - Nourhan Hisham Shady; Fatma Alzahraa Mokhtar; Hend Samy Abdullah; Salah A. Abdel-Aziz; Soad A. Mohamad; Mohamed S. Imam; Sherin Refat El Afify; Usama Ramadan Abdelmohsen (MDPI AG, 2024)
The aim of this study is to evaluate the anti-HPV potential of a Moringa olifera Lam seed, Nigella sativa L. seed, and Musa Acuminata peel herbal mixture in the form of polymer film-forming systems. A clinical trial conducted in outpatient clinics showed that the most significant outcome was wart size and quantity. Compared to the placebo group, the intervention group's size and number of warts were considerably better according to the results. Chemical profiling assisted by LC-HRMS led to the dereplication of 49 metabolites. Furthermore, network pharmacology was established for the mixture of three plants; each plant was studied separately to find out the annotated target genes, and then, we combined all annotated genes of all plants and filtered the genes to specify the genes related to human papilloma virus. In a backward step, the 24 configured genes related to HPV were used to specify only 30 compounds involved in HPV infection based on target genes. CA2 and EGFR were the top identified genes with 16 and 12 edges followed by PTGS2, CA9, and MMP9 genes with 11 edges each. A molecular docking study for the top active identified compounds of each species was conducted in the top target HPV genes, CA2 and EGFR, to investigate the mode of interaction between these compounds and the targets' active sites.